G14 Are Healthcare Professionals able to Estimate the Surface Area of a Burn in a Child?. (7th April 2014) - Fussell, T; Blackburn, F; Ross, J
Abstract : Aims: When different Healthcare Professionals estimate the surface area of a burn there can be significant discrepancies. This is particularly true in Paediatrics, where there are several methods commonly used to make this calculation. Errors in estimation may have a real impact on the acute management of a child. Accuracy is required across the multidisciplinary team. This study assesses this accuracy of estimations at different point along the pathway from pre-hospital to the Paediatric Emergency Department and the specialist paediatric burns unit. Method: Using a resuscitation mannequin we constructed a burn on the torso with a pre-determined surface area of 3% of the Total Body Surface Area (TBSA), according to both the Palmar method and the Lund & Browder Chart. Healthcare Professionals were asked to estimate the surface area of this burn, and to state how they had come to this answer. It was decided that an estimation of ≥10% TBSA would impact either the referral process or initial management. Results: 82 people took part with estimates ranging from 2.8–20% TBSA. 98% of participants overestimated the surface area with 16% estimating ≥10% TBSA. The degree of overestimation was far more pronounced in ambulance staff and GPs and the most accurate assessment was by the burns team. A range of methods were used to estimate the surface area, including the Palmar method, the Lund & Browder Chart and a number of other techniques. See Figure 3 below. Conclusion: This study has shown that Healthcare Professionals overestimate the surface area of a burn. This could have significant implications on the acute management of a child. This study supports both the need for regular training and the introduction of digital imaging liaison with burns units as a means to improve the treatment of acute burns in children.